A critical review on Rashtriya Arogya Nidhi scheme in India - Krishnamoorthy, Yuvaraj; Sakthivel, Manikandanesan; Sarveswaran, Gokul (International Journal Of Community Medicine And Public Health, 2018)
Patients with life threatening diseases were not able to seek care in tertiary care settings in spite of availability of facilities because of the cost of care involved. This hampers the nation’s progress towards Universal Health Coverage (UHC) by causing inequity in health service utilization and lack of financial protection to the families of the patient suffering from major diseases. Several government financial benefit schemes, both at central and state level, are available to cover the cost of care involved in the patients belonging to below poverty line (BPL) families. However, Rashtriya Arogya Nidhi is the only scheme which has been envisaged for providing comprehensive tertiary care benefit for patients with life threatening diseases belonging to BPL families. No government health programmes offers as much cash benefit as this scheme has been providing. This scheme, if utilized effectively can bring down the out-of-pocket expenditure considerably among the patients belonging to below poverty line families as well as increases the equity in utilization of tertiary care services. Even though the scheme was introduced two decades before, it has not been debated much for its utilization, impact, limitations and scopes for further improvement. Hence this review aims to critically appraise the strengths and limitations of the Rashtriya Arogya Nidhi scheme.